Sexual Minority Women's Experiences With Sexual Identity Disclosure in Contraceptive Care. Issue 5 (May 2019) - Greene, Madelyne Z.; Carpenter, Emma; Hendrick, C. Emily; Haider, Sadia; Everett, Bethany G.; Higgins, Jenny A.
Abstract : OBJECTIVE: To describe a group of young sexual minority women's experiences with and preferences for sexual identity disclosure in the context of contraceptive care. METHODS: In Chicago, Illinois, Salt Lake City, Utah, and Madison, Wisconsin, investigators conducted five focus groups (n=22) and 11 interviews with women aged 20–30 years who identified as something other than heterosexual. Focus groups explored social norms regarding contraceptive care; interviews documented individual experiences with contraceptive care. Using a qualitative descriptive approach and combined deductive and inductive content analysis, investigators coded transcripts for themes related to disclosing sexual orientation to contraceptive providers. RESULTS: Participants described the process of sexual identity disclosure in contraceptive care in three stages: 1) listening for whether, when, and how health care providers asked about sexual orientation, 2) deciding whether or not to disclose sexual identity to providers, and 3) evaluating responses from providers after disclosure. Participants wanted providers to: avoid assumptions and ask about both sexual identity and sexual behaviors, signal their openness and competence around the health of sexual minority women during contraceptive encounters, and focus discussions on the individual patient's priorities and needs for contraceptive care. CONCLUSION: Decisions made by sexual minority women about sexual identity disclosure in contraceptive contexts are influenced by previous and current interactions with health care providers. Contraceptive providers should ask all patients about sexual identity and sexual behavior, avoid assumptions about use of and need for contraception, and acknowledge the prevalence of marginalization, discrimination, and stigma experienced by sexual minority women and their communities in health care contexts. Abstract : Sexual minority women make nuanced decisions about sexual identity disclosure in contraceptive contexts; providers should avoid assumptions and acknowledge stigma commonly experienced in health care contexts.